(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
Today, there is an increased interest in digitalization of education and network communications, especially in the education system, all over the world, and its further development is accompanied by the introduction and direct connection with it. The article analyzes the best and worst sides of this direction, its use in teaching and development of students’ worldview.